Optimum pH for iron removal in groundwater using powdered activared carbon coagulant / Khairi Khalid, Elias Mohd Den and Mohd Razmi Zainuddin - Khalid, Khairi; Mohd Den, Elias; Zainuddin, Mohd Razmi (2008)
The objection to high concentrations of iron in groundwater is due to its objectionable colour, taste and odour. Iron is concentrated in water by contact with rocks and minerals and it is understandable that it is usually groundwater supplies that may require treatment for high levels of iron. The optimum pH for the removal of iron in ferruginous water was investigated. The investigation involved an analysis of the treatment through carrying out the standard jar test experiment for the determination of residual iron of the supernatant. The experimental results showed that the optimum iron removals were achieved at pH of 5.2 to 8.4 with the optimum pH of 6.34 and the dose of about 25 mg/l with an almost 87.5% removal rate. The concentration of residual iron in treated water by Powdered Activated Carbon (PAC) under optimum coagulant conditions was 0.12 mg/l, which can completely comply with the permissible limit of 0.30 mg/l. The data obtained from this experimental research hopefully is going to provide useful technical information for possible full domestic applications to remove and reduce the undesirable excess iron from any groundwater sources to its acceptable standard permissible limit.